INPUTS OPTIMIZATION IN THE SEEDLINGS PRODUCTION OF Corymbia citriodora E Eucalyptus dunnii - Costella, Claudia; Araujo, Maristela Machado; Pasquetti Berghetti, Álavro Luís; Aimi, Suelen Carpenedo; Santos de Lima, Marllos; Griebeler, Adriana Maria (Floresta, 2022)
Corymbia citriodora and Eucalyptus dunnii are species of relevant importance due to the quality of the wood and growth potential in Southern Brazil. Therefore, we aimed to identify containers and doses of controlled-release fertilizer capable of enhancing the morphophysiological quality and growth of these species in the nursery, aiming for the proper management of these inputs. The seedlings were produced in two volumes of containers (50 e 110 cm³), filled with Sphagnum peat-based substrate, mixed with different doses of controlled-release fertilizer (CRF) NPK 15-09-12 (0, 3, 6, 9 e 12 g L-1 of substrates). In addition, the morphological (height, stem diameter, leaf area, dry weight of shoot, root, and total) and physiological (chlorophyll a and b index and quantum yield of the photosystem II) attributes were evaluated. The morphological attributes proved to be suitable indicators of the quality of C. citriodora and E. dunnii seedlings, allowing to recommend the container of 50 cm³ and the doses of 9.0 g L-1 of controlled-release fertilizer for both species. At the same time, the physiological variables evaluated were not responsive to the effect of the treatments.